Falk Gernegroß - fleur de sel - Tannert, Christoph 1955-; Tupan, H. R. 1958- (Lubok Verlag, 2023)
Gernegroß’ paintings balance between aesthetic pleasure and uncanniness. The unnaturally colorful and hyper-polished bodies are reminiscent of commercial images flooding fashion magazines and Instagram feeds. Yet, the moments depicted are those of intimacy, meant to be kept to oneself. More than erotic, his paintings are gently pornographic in their manner of actively performing their relation to the viewer. Oftentimes, his visual references create a chemical reaction that reveal ironic, humorous and exciting intersections of high and popular culture. (Galerie Kleindienst)
Mit Texten von Christoph Tannert und Harry Tupan und einem Interview mit Falk Gernegroß, geführt von Dan Thawley
Auflage: 700
Keywords: Gernegroß, Falk -- 1973-; Sexualität; Motiv; Aktmalerei; Malerei; Bildband; Interview